Guest editorial: The impact of the COVID-19 pandemic on Islamic finance and environmental, social and corporate governance (ESG) - Hassan, Kabir M.; Saba, Irum; Shaikh, Salman Ahmed (Emerald Publishing, 2024)
While there are significant differences in resiliency and performance between Islamic banks and conventional banks – where Islamic financial institutions have shown positive results in some studies – there is evidence that these institutions must further develop instruments and governance that align themselves with sustainable development goals and greener economy. Trends in global economies and markets favor ESG screening and strict governance with relevant disclosure. If Islamic financial institutions can outpace conventional institutions in such regards, it can mitigate uncertainty risks in future shocks based on what we have seen in the aftermath of the COVID-19 shock.